(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
Abstract The results of the study showed the superiority of the alcoholic extract of propolis in reducing the infection of Nosema on honey bees to the lowest levels, as it reduced the number of spores to the lowest possible number, especially when using treatment with protein feeding, with an average of 214.20 spores / bee, which reflected positively on the physiological and vital characteristics of the bee’s body (age of the bee). Rectal acidity, moisture content of the bee’s body, and fat content of the bee’s body) which these characteristics are considered as evidence of the health of the bee’s body, with averages of (50.10 days, PH 4.95, 64.52%, and 81.60%), respectively, which did not differ significantly from the percentages of most of the above traits. The male of the extract, but when adding the treatment with sugary nutrition, followed it in reducing the infection rate when using the treatment with the aqueous extract, which achieved good and satisfactory results, while the infection was high and the coefficients values were low in the comparison treatment, and the highest average number of spores was 2988.70 spores / bee, which was reflected negatively on the physiological characteristics, vitality, activity, and health of honey bees, which amounted to (21.10 days, PH 5.85, 89.74%, and 5.95%), respective